(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2011)
Dextromethorphan is a dissociative antitussive agent which is being sold freely as an over the counter drug in combination or solo in the form of tablets or syrups. The desire to be one of a kind amongst their peers is causing adolescents to experiment with different drugs. The problem is complicated with the free information available on internet regarding the new and the latest use of this drug which this savvy generation has easy access to. The recreational use of DXM is rising at a very fast pace in India and esp. Punjab. The menace needs to be checked on priority if we want to save our youth from the demon of drugs.